Hubungan Pemberian Motivasi Terhadap Prestasi Kerja Karyawan pada Hotel Resty Menara Pekanbaru - Rifky, Muhammad Yanuar; Sutrisna, Endang (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
This study raises the issue of the relationship of motivation on employeeperformance in Resty Menara Hotel Pekanbaru. The companies need to motivateemployee performance can be increased, therefore the management companyshould provide different forms of motivation to pay attention to needs ofemployees. This study refers to the ERG theory of Clayton Alderver (1972) whichsays that there are three human needs, namely eksistence, relatedness and grow.Population in this study was a hotel employee Resty Menara Pekanbaru, while thedata collection is used questionnaires, interviews and documentation.measurement technique using a likert scale with answers that were given a scoreof 1-5, while the tools of statistical tests in this study is the correlation coefficient.Calculation based on SPSS version 17 for Windows value of the correlationcoefficient of 0.716 which has a value of 0.716 level means there is a strongrelationship. strong relationship of motivation to employee Resty Menara hotelPekanbaru. By t test can be know that t test by (8,706) > t table (3,431) with Sig.(0,000) < 0,05. With the result of t is greater than t table, this means that the workmotivation variables significantly influence job performance. The conclution ismotivation in view of the need existence, relatedness and needs grow undertakenResty Menara Hotel Pekanbaru be effective and can be good categorized. overallemployee has been carrying out duties in accordance with operational standardsprosedure that have been set by Resty Menara Hotel.Keywords : motivation, performance, human resources